Quatremère de Quincy's Moral Considerations on the Place and Purpose of Works of Art: Introduction and Translation - Quatremère de Quincy, Antoine Chrysostome (Lexington Books, 2021)
Antoine Chrysostome Quatremère de Quincy (1755-1849) was the most important Neoclassical art historian in the generation after Johann Joachim Winckelmann (1717-1768). It is difficult now to appreciate his importance, due in part to the lack of translations of his 21 published books: three were rendered into English in the 19th century, and one in the 21st. The Moral Considerations has long been considered the most shattering polemic against public museums ever written. But I will show that Quatremère’s polemic was aimed, not against museums per se, but rather against the imperialist and secularist curatorial purposes of Parisian museums in the age of Revolution. His Neoclassical commitments maintained the centrality of religion, and of incarnation, to any proper understanding of the place and purpose of the fine arts.